On the Conditional Effects of IMF Loan Program Participation on Output Growth - Michael Binder; Marcel Bluhm (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2014)
The empirical evidence currently available in the literature regarding the effects of a country's IMF program participation on its output growth is rather inconclusive. In this paper we propose and estimate a panel data sample selection model featuring state dependence. As in this model the output growth effects of program participation can be conditional on the realization of a state variable (conditional pooling), our framework may reconcile previous empirical evidence based on models without state-dependent effects. We find that the effects of IMF program participation on output growth vary systematically with an index reflecting a country's institutional record, and that output growth effects of program participation are significantly positive only if the program participation is coupled with sufficient improvement of the institutional record.
urn:nbn:de:hebis:30:3-343188
Keywords: O11; O19; C33; 330; Conditional Pooling; IMF Program Participation; Output Growth; Panel Sample Selection Models